Axial and Peripheral Articular Manifestations in Inflammatory Bowel Disease Patients in Tishreen University Hospital in Latakia-Syria - Ebraheem, Rasha mohammad Haj; Hassan, AbdAlrazak; Madi, Maher (Journal of medical and pharmaceutical sciences, 2022)
The objective is to study the axial and peripheral articular manifestations in inflammatory bowel disease patients and to study the pattern of the manifestations and its relationship with the extent of the intestinal disease. Materials and Methods: The study began in March 2020 and ended in April 2021, in GI Unit and clinic in Tishreen University Hospital-Latakia. 61 IBD patients were recruited, a full medical history was taken and a full physical examination of the musculoskeletal system was performed, a pelvis x-ray was done when needed. Results: 61 IBD patients were studied, 34(55.7%) with Crohn’s disease and 27(44.3%) with ulcerative colitis. articular manifestations of any type were present in 45.9 % (28 of 61 patients), 53.5 %( 15 with Crohn’s disease) and 46.4 %( 13 with ulcerative colitis). Peripheral manifestations were present in 25.8 %( 14.7% with CD and 11.1% with UC. Axial manifestations were present in 22.9 %( 11.8% with CD and 11.1%with UC). Both axial and peripheral disease were present in 43.5%. Among those with peripheral manifestations, (45.7%) had type 1 arthritis (pauciarticular) (23.3% with CD and 22.2% with UC) and (13.3%) had type 2 arthritis (polyarticular) (5.9% with CD and 7.4% with UC). 36.6% had enthesitis (14.7% with CD and 22.2% with UC), 12.5% had Dactylitis (8.8% with CD and 3.7% with UC). 7.4% had AS (ankylosing spondylitis) (two patients with UC). Conclusions: the results of our study of articular manifestations in patients with IBD are close to the results of other studies in the region and to the global ones. Peripheral manifestations were more prevalent than axial. And Ankylosing spondylitis was not that common.